2017
DOI: 10.1063/1.4999375
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical characteristics of potential candidate lead-free BiFeO3-BaTiO3 piezoelectric ceramics

Abstract: The crystal structures and electrical properties of lead-free BiFeO3-BaTiO3 [(1-x)BFxBT] piezoelectric system are investigated as a function of BaTiO3 concentration. The well-saturated P-E hysteresis loop was observed in the 0.80BiFeO3–0.20BaTiO3 composition system, while a less hysteretic strain-electric field curve was exhibited by the 0.70BiFeO3–0.30BaTiO3 with a strain hysteresis of 16%, the value comparable to PZT-based piezoelectric ceramics. The crystal structures investigated under the synchrotron radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(79 citation statements)
references
References 56 publications
7
72
0
Order By: Relevance
“…The compounds in vicinity of the rhombohedral-pseudocubic phase boundary are characterized by increased piezoelectric coefficient d 33 , reaching maximum value of about 250 pm/V in the compounds with 33% of BaTiO 3 content. It should be noted that structural state of the solid solution with one-third of BaTiO 3 content is characterized by the dominant pseudocubic phase with minor (~35%) fraction of the rhombohedral phase [37][38][39]. Moreover, our recent investigation involving the piezoresponse force microscopy measurements has revealed a polarizable state in compounds with x~0.33, 0.35, while according to the XRD data, these compounds possess single phase cubic structure [37].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The compounds in vicinity of the rhombohedral-pseudocubic phase boundary are characterized by increased piezoelectric coefficient d 33 , reaching maximum value of about 250 pm/V in the compounds with 33% of BaTiO 3 content. It should be noted that structural state of the solid solution with one-third of BaTiO 3 content is characterized by the dominant pseudocubic phase with minor (~35%) fraction of the rhombohedral phase [37][38][39]. Moreover, our recent investigation involving the piezoresponse force microscopy measurements has revealed a polarizable state in compounds with x~0.33, 0.35, while according to the XRD data, these compounds possess single phase cubic structure [37].…”
Section: Introductionmentioning
confidence: 89%
“…Simultaneous doping at the A-and B-positions of the perovskite lattice allows to modify the sub-lattices responsible for polar and magnetic orders [35][36][37]. Thus, in compounds Bi 1−x Ba x Fe 1−x Ti x O 3 , an increase of the dopant content leads to structural transition from the polar rhombohedral phase to the polar tetragonal phase through the formation of an intermediate (pseudo)-cubic structure [8,[37][38][39]. The compounds in vicinity of the rhombohedral-pseudocubic phase boundary are characterized by increased piezoelectric coefficient d 33 , reaching maximum value of about 250 pm/V in the compounds with 33% of BaTiO 3 content.…”
Section: Introductionmentioning
confidence: 99%
“…4) Among the various lead-free piezoelectric ceramics, the Bi-based systems have attracted attention due to their high spontaneous polarization and large piezoelectric response. 5), 6) It has been reported that the pure (Bi 0.5 Na 0.5 )TiO 3 (BNT) has a large remanent polarization (P r = 38¯C/cm 2 ) 7) and a low piezoelectric coefficient (d 33 = 58 pC/N). 8) Moreover, a large piezoelectric coefficient was observed at MPB compositions of (Bi 0.5 Na 0.5 )TiO 3 BaTiO 3 (BNTBT) 9), 10) and (Bi 0.5 Na 0.5 )TiO 3 (Bi 0.5 K 0.5 )TiO 3 (BNTBKT) solid solutions.…”
Section: )3)mentioning
confidence: 99%
“…Journal of the Ceramic Society of Japan 126 [5] 316-320 2018 strain properties of the BF33BT lead-free piezoelectric ceramics. The ferroelectric property was investigated by a polarizationelectric field (PE) hysteresis loop, which was measured by an AC bias with a frequency of 0.1 Hz at room temperature is shown in Fig.…”
Section: Figure 2 Shows Ferroelectric and Electric-field-inducedmentioning
confidence: 99%
“…(a) The direct piezoelectric effect provides an electric charge upon application of a mechanical stress, whereas (b) the converse piezoelectric effect describes the situation where strain develops under an applied electric field. 30 Similarly, it was demonstrated that an air quenching treatment in BF-BT affords an improvement in piezoelectric properties through salient changes in atomic structure.…”
mentioning
confidence: 98%